Cadar, Isbal And Cultural Da'wah Problems In Normative-Historical Islam: An Overview Of Da'wah Communication - Rahmawati, Endang; Zulkifli, Muhammad (KOMUNIKA, 2023)
Islam is a religion brought by the Prophet Muhammad sallallaahu ‘Alaihi Wasallam which is a mercy for the universe. But lately, there have been several issues of cornering Islam, namely Islamophobia. This is because sometimes the application of Islam normatively and also its application in the real world that we call the term historical Islam occurs in conflict things, so in this case the approach of humanism, the wisdom of thinking, mutual respect and mutual respect in order to create a safe life and peace. The data analysis method that the researcher uses is a descriptive analysis method, which explains the data with the elaboration based on theories, one of the theory is M. Amin Abdullah's theory of normative and historical Islam. This research is in the form of library research. The results of this study are the solution to the normative and historical problem of Islam, namely missionary communication that is humanist, advising, embracing, not criticizing and not forcing and remaining in the arms of ukhuwah Islamiyah as long as these differences can still be tolerated and does not come out of the boundaries of sharia 'at Islam itself. Why does humanist da'wah communication become a middle way to reconcile normative or historical understanding? Because in fact the problem is not the difference itself, but how we respond to these differences.